Efeito da concentração de soro e da adição de culturas na sinérese e pós-acidificação de bebida láctea fermentada - Laura Caroline Ferreira Mendes Capuchinho (2018)
Whey has proven to be a valuable co-product used in the food industry because of its low cost, excellent amino acid profile and the benefits it offers to human health. In addition, its application in the industry can be explained by being considered an effluent, with negative environmentalimpact. Thus, one of the main alternatives for the use of whey comprises the formulation of dairy drinks. The objective of the study was to investigate the influence of the addition of different cultures and concentrations of whey in post-acidification and stability of the fermentedmilk beverage gel (BLF) during shelf life. The BLF was elaborated in the Laboratory of Dairy Technology of the Institute of Agrarian Sciences. For the experiment three different commercial thermophilic cultures were used for yoghurt, consisting of strains of Lactobacillus bulgaricus andStreptococcus thermophilus. For each culture dairy drinks containing 0%, 20%, 30% and 40% of whey were prepared in their formulation. Subsequently, the BLF samples were stored under refrigeration at 5 ± 1 ° C and analyzed for pH, acidity, and syneresis at 2; 10; 20 and 30 dayspost manufacture. The parameters of acidity, pH and syneresis were synthesized in a single main component from Principal Component Analysis (PCA). To do so, they were previously staggered to eliminate the difference of the different magnitude scales of each variable usingthe standard deviation transformation (xi-mean / standard deviation). It was verified that, in relation to the cultures used, there was no difference between them in the analyzed parameters. On the other hand, the concentration of serum influenced the syneresis and acidity of theproduct, and the drink with the highest percentage of serum presented higher syneresis and the one containing the lower percentage of serum presented lower acidity. For pH values, it was not possible to determine which concentration had higher or lower pH. Thus, the use of differentcultures did not influence the final product, but the different serum concentrations influenced the characteristics of the product.